Ginsenoside Rb1 promotes intestinal epithelial wound healing through extracellular signal‐regulated kinase and Rho signaling. Issue 7 (22nd November 2018) - Toyokawa, Yuki; Takagi, Tomohisa; Uchiyama, Kazuhiko; Mizushima, Katsura; Inoue, Ken; Ushiroda, Chihiro; Kashiwagi, Saori; Nakano, Takahiro; Hotta, Yuma; Tanaka, Makoto; Dohi, Osamu; Okayama, Tetsuya; et al.
Abstract: Background and Aim: Daikenchuto, a traditional Japanese herbal medicine, has been reported to exhibit anti‐inflammatory effects against intestinal inflammation. However, whether daikenchuto has a therapeutic effect against intestinal mucosal injuries remains unclear. Thus, the aim of this study was to determine the effect of daikenchuto on intestinal mucosal healing. Methods: Colitis was induced in male Wistar rats by using trinitrobenzenesulfonic acid. Daikenchuto (900 mg/kg/day) was administered for 7 days after the induction of colitis. Thereafter, intestinal mucosal injuries were evaluated by determining the colonic epithelial regeneration ratio ([area of epithelial regeneration/area of ulcer] × 100). Restoration of rat intestinal epithelial cells treated with daikenchuto and its constituent herbs ( Zanthoxylum fruit, processed ginger, and ginseng) and ginsenoside Rb1, which is a ginseng ingredient, was evaluated using a wound‐healing assay. Results: The colon epithelial regeneration ratio in the daikenchuto‐treated rats was significantly higher than that in the control rats. Daikenchuto, ginseng, and ginsenoside Rb1 enhanced wound healing, and the ginsenoside Rb1‐induced enhancement was inhibited by extracellular signal‐regulated kinase and Rho inhibitors. Conclusions: Daikenchuto and its constituent, ginsenoside Rb1, promoted wound healing. Because mucosal healing is one of the most important therapeutic targets in patients with inflammatory bowel disease, ginsenoside Rb1 may be a novel therapeutic agent against intestinal mucosal damage such as that occurring in intestinal bowel disease.